Home-Based Exergames for Older Adults Balance and Falls Risk: A Systematic Review. (3rd July 2021) - Alhagbani, Abdulrhman; Williams, Alison
Abstract: Aims: To evaluate whether unsupervised home-based exergames can improve balance and reduce falls risk among older people, with the reported adverse events being considered as a secondary objective. Methods: A systematic search of CINAHL, Medline Ovid, EMBASE Ovid, Ovid Emcare, AMED Ovid, PEDro, Cochrane and JBI was carried out. Each study was critically appraised using the JBI checklists. Results: Of the 7 studies, a statistically significant improvement in balance outcomes was demonstrated in 5 studies. Of the 7 studies, 3 studies examined falls risk using the Physiological Profile Assessment (PPA), all of which showed a statistically significant reduction. Five studies revealed no adverse events, while 1 study reported neck and hip strain. Conclusion: Current evidence indicates that unsupervised home-based exergames reduced falls risk. Balance improved within-group, but evidence remains inconclusive when compared to no intervention or exercises. Muscle strain was reported as a result of exergaming in an unsupervised environment.